Loop Myopexy Surgery for Strabismus Associated with High Myopia - Su, Yun (J Ophthalmol, 2016)
Strabismus associated with high myopia is a rare abnormality of ocular motility, leading to the impairment of abduction and supraduction. Loop myopexy of the superior rectus (SR) and lateral rectus (LR) muscles is now the most preferred surgery for restoring the dislocated eye globe back into the muscle cone. Various procedural modifications have been made based on this concept, and satisfactory outcomes have been reached in most cases. In this paper, we review various surgical modifications published in the literature that are based on the loop myopexy surgery in patients with high myopic strabismus and summarize the applicable scope of different surgical procedures for patients with different degrees of strabismus. Three major surgical procedures are identified and different modifications have been applied based on their concept. Most of these modifications have been proven to be safe and effective and result in good ocular alignments. The selection of such modifications is of great importance in different patients. Careful evaluation before surgery should be made not only to make the correct diagnosis but also to choose an appropriate surgical procedure and offer individualized modifications in the surgery.